Combined neurothrombectomy or thrombolysis with adjunctive delivery of 3K3A-activated protein C in acute ischemic stroke - Amar, Arun Paul; Griffin, John H.; Zlokovic, Berislav V. (Frontiers in Cellular Neuroscience, 2015)
In the treatment of acute ischemic stroke, vessel recanalization correlates with improved functional status and reduced mortality. Mechanical neurothrombectomy achieves a higher likelihood of revascularization than intravenous thrombolysis, but there remains significant discrepancy between rates of recanalization and rates of favorable outcome. The poor neurological recovery among some stroke patients despite successful recanalization confirms the need for adjuvant therapy, such as pharmacological neuroprotection. Prior clinical trials of neuroprotectant drugs failed perhaps due to inability of the agent to reach the ischemic tissue beyond the occluded artery. A protocol that couples mechanical neurothrombectomy with concurrent delivery of a neuroprotectant overcomes this pitfall. Activated protein C (APC) exerts pleiotropic anti-inflammatory, anti-apoptotic, antithrombotic, cytoprotective, and neuroregenerative effects in stroke and appears a compelling candidate for this novel approach.